Internalisasi Pemahaman Hukum Nikah melalui Kajian Kitab Taqrib (Matn Abu Syuja’) di Pondok Pesantren Raudlatul Muhibbin Al-Mustainiyyah Surakarta - Sintia Devi Astuti Dwi Cahyani; Tsania Nur Syahadatina; Wahyu Setiawan; Roisah Masuliyah (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
Marriage is an innate bond between a man and a woman as husband and wife with the aim of maintaining offspring and channeling human nature according to religious guidance. This study aims to describe the understanding of marriage law through the study of the book of Taqrib (Matn Abu Syuja') at the Raudlatul Muhibbin Al-Mustainiyyah Islamic Boarding School in Surakarta. The method used is descriptive qualitative with in-depth interview techniques as the main instrument. The research subjects consist of students and ustaz who are active in the study of marriage fiqh. The results of the study show that the process of understanding marriage law takes place through three main stages. First, students receive new knowledge through reading books that are corrected directly by the teacher. Second, there is a value transaction through group discussions and deliberation that strengthens understanding and forms a critical attitude towards contemporary issues. Third, students carry out simulation practices and case studies such as serial marriage, underage marriage, and intersectarian marriage which are linked to positive Indonesian law. This process demonstrates the integration between the understanding of classical texts and the context of modern law. This study recommends strengthening the contextual approach in the study of marriage jurisprudence and the development of case-based learning methods to increase the relevance and understanding of Islamic law in the pesantren environment.